Gas microchannel plate core glass, glass rod, and methods of making and using the same
Patent Information
- Application Number
- CN202611374623.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-27
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of optoelectronic materials technology, and in particular to a gas microchannel plate core glass, a glass rod, its preparation method, and its application. Background Technology
[0002] Gas microchannel plates (GMCPs) are core multiplier devices for amplifying weak signals in gas pixel detectors, and are also key components for direct verification of the Migdall effect in neutral particle collisions and detection of low-energy nuclear recoil in light dark matter. Unlike traditional vacuum microchannel plates, GMCPs operate under long-term immersion in a mixed ionized gas environment of helium and dimethyl ether, placing extremely stringent requirements on the global resistivity uniformity, gas corrosion resistance, ultra-low gas release, and low ion diffusion of the glass inner wall of the channel. A complete GMCP is fabricated from a skin glass and a core glass through processes such as bundling, wire drawing, hot pressing, and acid etching. The skin glass performs electron multiplication, while the core glass serves as a selectively acid-etched sacrificial layer. The high degree of matching between the thermal, mechanical, and chemical properties of the two is fundamental to ensuring the final channel morphology, electric field uniformity, and long-term detection stability.
[0003] Currently, the industry has developed corrosion-resistant, low-gas-release skin glass suitable for GMCP, but the corresponding core glass still has significant technical shortcomings, becoming a key bottleneck restricting the improvement of GMCP detection performance. Existing conventional core glasses generally use a high borosilicate system. During high-temperature drawing and hot-pressing, boron easily diffuses and permeates into the skin glass, causing lead and bismuth enrichment on the surface, significantly deviating from the 1-10 GΩ global resistance range required for GMCP. This results in disordered resistance distribution within the channel, with single-channel resistance deviations exceeding 10%. Uneven resistance directly causes distortion of the electric field inside the channel. The weak common-vertex signal at the single-electron level generated by the Migdall effect is easily masked by ion feedback noise, making effective identification of low-energy nuclear recoil characteristic tracks impossible. Furthermore, traditional core glasses often use small-ionic-radius alkali metals such as sodium oxide and potassium oxide as fluxing components. During high-temperature processing, Na… + K +Continuous penetration and diffusion into the inner wall of the core glass disrupts the dense silicon-oxygen network structure, reducing its resistance to helium penetration and dimethyl ether chemical corrosion. This exacerbates the deterioration of the inner wall roughness under plasma ion bombardment, leading to device gain attenuation and a significant reduction in lifespan after long-term operation. Furthermore, the thermal expansion coefficient and softening temperature of existing core glass are poorly compatible with those of GMCP-specific core glass. The mismatch in deformation and softening behaviors of the two types of glass during the bundle drawing and high-temperature hot pressing processes easily results in defects such as bundle breakage, channel deformation, hexagonal array collapse, and core-skin delamination, significantly reducing product yield and making it difficult to fabricate high-precision GMCP arrays with high aperture ratios and 200,000-channel consistency. Existing core glass cannot simultaneously meet the three core requirements of low element interdiffusion, controllable and uniform acid etching, and matching thermal properties. Moreover, mainstream formulations rely on sodium, potassium, and alkali metals, as well as high boron components, making them unsuitable for the ultra-low noise, long lifespan, and high-precision signal amplification requirements of Migdall detection scenarios. Summary of the Invention
[0004] The main objective of this invention is to provide a core glass for a gas microchannel plate, a glass rod, its preparation method, and its application. The technical problem to be solved is how to provide a core glass that is acid-etched in a controllable and uniform manner and whose thermal properties match those of the outer glass. A barrier film is set on the surface of the core glass rod so that after the core glass rod and the outer glass are combined, the deformation remains consistent during the bundle drawing and high-temperature hot pressing processes, and the interpenetration of elements at the core-outer interface is significantly reduced. This ensures uniform resistance and regular channel array across the entire gas microchannel plate, enabling ultra-low noise, long lifespan, and high-precision amplification of weak signals in the Migdall effect detection scenario.
[0005] The objective of this invention and the technical problem it solves are achieved by the following technical solution. According to this invention, a gas microchannel plate core glass is composed of the following components by mass percentage of oxides: SiO2, 5-15 wt%; B2O3, 10-20 wt%; La2O3, 20-30 wt%; BaO, 10-20 wt%; SrO, 5-10 wt%; In2O3, 2-7 wt%; Sm2O3, 5-10 wt%; Rb2O, 5-10 wt%; Cs2O, 5-10 wt%.
[0006] The objectives of this invention and the technical problems it addresses can be further achieved by the following technical measures.
[0007] Preferably, the core glass of the gas microchannel plate is composed of the following components by mass percentage of oxides: SiO2, 8~12wt%; B2O3, 12~18wt%; La2O3, 22~28wt%; BaO, 12~18wt%; SrO, 6~9wt%; In2O3, 3~6wt%; Sm2O3, 6~9wt%; Rb2O, 6~9wt%; Cs2O, 6~9wt%.
[0008] Preferably, in the core glass of the gas microchannel plate, the mass ratio of the sum of La2O3 and Sm2O3 to B2O3 is 1.25~2.50; and the ratio of the sum of the mass of BaO and SrO to the sum of the mass of La2O3 and Sm2O3 is 0.69~1.20.
[0009] Preferably, in the core glass of the gas microchannel plate, the mass ratio of the sum of La2O3 and Sm2O3 to B2O3 is 1.6~2.0; and the ratio of the sum of the mass of BaO and SrO to the sum of the mass of La2O3 and Sm2O3 is 0.8~1.0.
[0010] Preferably, the softening temperature T of the core glass of the gas microchannel plate is... f The coefficient of thermal expansion is 82×10⁻⁶ at temperatures ≥660℃ and between 20 and 300℃. -7 / ℃ ~87×10 -7 / ℃, no crystallization or phase separation at 600~900℃; the acid resistance stability of the core glass tested according to GB / T 7962.14-2010 is Class 6.
[0011] The objective of this invention and the technical problem it solves are achieved through the following technical solution. A method for preparing a glass rod as the core material for a gas microchannel plate according to this invention includes the following steps: S1 prepares the core glass material according to the aforementioned gas microchannel plate formulation; adds 0.1~0.3wt% of clarifying agent to the preparation and mixes it evenly; S2 The mixture is placed in a quartz crucible and first melted at 1200~1300℃ to obtain pre-sintered clinker; S3 places the calcined material in a high-purity platinum crucible with niobium dispersion, and heats it to 1450~1500℃ for a second melting under the stirring condition of a platinum-rhodium alloy stirring rod. After clarification, a homogenized glass melt is obtained. S4 cools the homogenized glass melt to 1350~1400℃ and then mechanically extrudes it to obtain a core glass blank rod. S5 heats the core glass blank rod to 500-580℃ at a rate of 1.5-3.0℃ / min, holds it at that temperature for 3-4 hours for annealing, and then cools it to room temperature at a rate of 0.5-1.5℃ / h. The S6 precision shaping and mirror polishing process yields the core glass rod.
[0012] The objective of this invention and the technical problem it solves are achieved by the following technical solution. A coating method for a glass rod as the core material of a gas microchannel plate, according to this invention, includes the following steps: S1 Surface treatment: The core glass rod prepared by the above preparation method is cleaned, dried and subjected to plasma etching pretreatment; S2 uses niobium as the target material and a reactive magnetron sputtering process to deposit a Nb2O5 barrier film on the surface of the core glass rod in an atmosphere of mixed argon and oxygen. The thickness of the barrier film is 50~200nm. S3 performs low-temperature stress annealing on the coated core glass rod by holding it at 400~450℃ for 1~3 hours.
[0013] The objectives of this invention and the technical problems it addresses can be further achieved by the following technical measures.
[0014] Preferably, in the coating method, the reactive magnetron sputtering process has an argon flow rate of 30-60 sccm, a working pressure of 0.3-0.8 Pa, an oxygen-argon volume flow rate ratio of 1:8-1:5, an RF sputtering power of 120-200 W, a target-substrate distance of 60-100 mm, and a core glass rod rotation speed of 5-10 r / min.
[0015] Preferably, in the coating method, the pretreatment includes: sequentially ultrasonically cleaning with anhydrous ethanol and deionized water for 10-15 min each, followed by vacuum drying at 80-100℃ for 30-40 min; the plasma etching is performed by argon plasma etching at 500V RF bias for 4-6 min.
[0016] The objective of this invention and the technical problem it solves are achieved by the following technical solution. A gas microchannel plate core material glass rod according to this invention is obtained by the aforementioned preparation method.
[0017] The objectives of this invention and the technical problems it addresses can be further achieved by the following technical measures.
[0018] Preferably, the core glass rod of the gas microchannel plate is coated with an Nb2O5 barrier film with a thickness of 50~200nm; after the core glass rod coated with the Nb2O5 barrier film is combined with the skin, the interdiffusion width at the core-skin interface is ≤50nm.
[0019] The objective of this invention and the technical problem it solves are achieved by the following technical solution. According to this invention, a gas microchannel plate is prepared by combining a sheathed glass tube and a core glass rod with a surface coated with an Nb2O5 barrier film, followed by bundling, drawing, hot pressing, and acid etching processes.
[0020] The objective of this invention and the technical problem it solves are achieved by the following technical solution. According to this invention, an application of the aforementioned gas microchannel plate core material glass in the preparation of gas microchannel plates, Migdall effect detection devices, or light dark matter detection devices is proposed.
[0021] By employing the above technical solutions, the present invention provides a gas microchannel plate core material glass, a glass rod, its preparation method, and its application. The beneficial effects are at least reflected in the following aspects: The core glass of this invention adopts a low boron composition design, with the B2O3 content controlled at 10~20wt%. This effectively reduces the diffusion and penetration of boron into the skin glass during high-temperature drawing and hot pressing, and avoids the enrichment of lead and bismuth on the surface of the skin glass. This maintains the uniformity of the global resistance of the skin glass in the range of 1~10GΩ, reduces single-channel resistance deviation, reduces electric field distortion and ion feedback noise, and is beneficial to the stable amplification of weak signals at the single electron level.
[0022] The core glass of this invention uses large-radius alkali metal oxides such as Rb₂O and Cs₂O instead of traditional Na₂O and K₂O. The large-radius alkali metal ions, compared to Na, provide a significant advantage. + K + The high-temperature cross-interface diffusion capacity is significantly reduced, which can inhibit the penetration of alkali metals into the glass substrate. This helps protect the dense silicon-oxygen network structure of the glass substrate, maintain its resistance to helium penetration and dimethyl ether corrosion, and slow down the deterioration of the inner wall roughness under plasma ion bombardment, thereby helping to extend the working life of the gas microchannel plate.
[0023] The core glass of this invention achieves a softening temperature (Tf≥660℃) and a coefficient of thermal expansion (82×10⁻⁶) that are well matched with the outer glass through the synergistic regulation of rare earth oxides La₂O₃ and Sm₂O₃, and the auxiliary fine-tuning of the coefficient of thermal expansion by alkaline earth metals BaO and SrO. -7 / ℃~87×10 -7 (600-900℃), and there is no crystallization or phase separation at 600-900℃, which ensures consistent core-skin deformation during the bundle drawing and high-temperature hot pressing processes, avoids defects such as bundle breakage, channel deformation, hexagonal array collapse, and core-skin delamination, and improves finished product yield and array accuracy.
[0024] The core glass of this invention generates a large amount of non-bridging oxygen and constructs nano-etching channels by combining alkaline earth metals BaO and SrO with rare dispersed metals In2O3. This can improve the glass's dissolution rate in dilute acid and achieve synchronous and uniform etching across the entire cross-section. Its acid resistance is Class 6, and it can be quickly and uniformly etched away by acid during the acid etching process, ensuring no residue in the acid-washed holes. This is beneficial for preparing microchannel arrays with high aperture ratio and high precision.
[0025] This invention involves coating the surface of the core glass rod with an Nb₂O₅ barrier film, which, together with the low-diffusion core material formulation, forms a dual protection. This creates a high ion diffusion barrier at the high-temperature contact interface between the core and the outer sheath, effectively blocking the bidirectional interdiffusion of elements such as B, Rb, and Cs in the core material with elements such as Pb and Bi in the outer sheath. This results in an interdiffusion width at the core-outer sheath interface ≤50nm, stabilizing the global volume resistivity of the gas microchannel plate and ensuring the uniformity of resistance and corrosion resistance of the outer sheath glass. This is suitable for ultra-low noise detection of weak single-electron signals due to the Migdall effect. Simultaneously, this barrier film only coats the outer surface of the core rod, without altering the core glass formulation itself, and does not disrupt the controllable and uniform etching characteristics of the core material in dilute acid. Furthermore, it can completely dissolve simultaneously with the core material during the acid etching process, leaving no film residue to block the microchannels, thus improving the gain consistency and long-term operational stability of the gas microchannel plate.
[0026] The core glass, glass rod, and their preparation and coating methods provided by this invention can be directly used to prepare high-performance gas microchannel plates, and can be further applied to Migdall effect detection devices and light dark matter detection devices to achieve ultra-low noise, long life and high precision weak signal amplification.
[0027] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below. Detailed Implementation
[0028] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the following detailed description, in conjunction with preferred embodiments, details the specific implementation methods and effects of a gas microchannel plate core material glass, glass rod, its preparation method, and its application according to the present invention. In the following description, different "embodiments" or "embodiments" do not necessarily refer to the same embodiment. Furthermore, the results of one or more embodiments can be combined in any suitable manner. These embodiments are provided to make the invention thorough and complete, and to fully express the scope of the invention to those skilled in the art. It should be noted that, unless otherwise specifically stated, the relative arrangement of components and steps, material composition, numerical expressions, and values described in these embodiments should be interpreted as merely exemplary and not as limiting.
[0029] Typically, core glass is composed of glass framework oxides, easily acid-soluble oxides, and network oxides that adjust viscosity, thermal and chemical stability, and improve material properties. The interactions of these glass components collectively determine the various properties of the glass. The applicant addresses the core glass of existing GMCP (Glass Metal Concentrate Powder) systems by designing a formulation that addresses key pain points such as high boron content, easy diffusion of small-radius sodium and potassium alkali metals into the skin glass at high temperatures, severe interpenetration at the core-skin interface, single-channel resistance deviation exceeding 10%, mismatch between thermal expansion and softening temperatures and the self-developed corrosion-resistant skin material, and low yield in wire drawing. The first step is to reduce the amount of B2O3 added to minimize boron migration across the interface; then, large-radius Rb2O and Cs2O are used to completely replace Na2O and K2O, weakening the diffusion ability of alkali metals. La2O3 and Sm2O3 rare earth oxides are introduced to synergistically regulate thermal parameters, achieving matching with the softening temperature and expansion coefficient of the skin glass, while simultaneously improving anti-crystallization performance. Combined with BaO, SrO alkaline earth metals, and In2O3 rare dispersed metals, a large amount of non-bridging oxygen is generated, increasing the glass acid dissolution rate and ensuring no residue during acid etching and hole formation. By limiting the total amount of rare earth / boron, alkaline earth / rare earth, and alkali metals, and the mass ratio of easily acid-soluble components / skeleton components, the three major requirements of low diffusion, easy etching, and thermal matching are balanced. Furthermore, a dense Nb2O5 barrier film is magnetron sputtered on the core rod surface, constructing an ion diffusion barrier at the core-skin contact interface. This, combined with the low-diffusion core material formulation, forms a dual protection, controlling the core-skin interpenetration width to within 50 nm, meeting the ultra-low noise detection requirements for weak single-electron signals due to the Migdall effect.
[0030] Based on the above-mentioned inventive concept, this invention proposes a gas microchannel plate core glass, which, based on the mass percentage of oxides, is composed of the following components: SiO2, 5~15wt%; B2O3, 10~20wt%; La2O3, 20~30wt%; BaO, 10~20wt%; SrO, 5~10wt%; In2O3, 2~7wt%; Sm2O3, 5~10wt%; Rb2O, 5~10wt%; Cs2O, 5~10wt%.
[0031] In the above technical solution, SiO2 is the basic structural oxide of the glass, used to build a continuous silicon-oxygen network, providing the glass with basic mechanical strength and intrinsic chemical stability, while controlling the high-temperature viscosity and coefficient of thermal expansion of the glass, ensuring the performance of bundle drawing and hot pressing. If the content is less than 5wt%, the continuous silicon-oxygen network is incomplete, the thermal stability of the glass deteriorates significantly, and phase separation and crystallization easily occur at 600~900℃, making it prone to wire breakage and bundle cracking during high-temperature drawing. If the content is higher than 15wt%, the silicon-oxygen network is too dense, the number of non-bridging oxygens inside the glass is greatly reduced, the acid resistance grade decreases, the acid dissolution rate is too low, and core material is easily left to block micropores after acid washing and pore making; at the same time, the glass melt viscosity increases significantly, making it difficult to achieve complete clarification and homogeneity in the melting range of 1450~1500℃, and easily generating internal defects such as sand and bubbles. Further preferred content is 8~12wt%.
[0032] B2O3 is a low-melting-point fluxing intermediate oxide that can lower the overall melting temperature of glass, optimize the properties of high-temperature wire drawing materials, moderately increase the non-bridging oxygen inside the glass, and help improve the acid etching rate. If the content is less than 10wt%, the fluxing effect is insufficient, the melting temperature requirement increases significantly, rare earth oxides are difficult to disperse uniformly in the glass system, and rare earth silicate crystal phases are easily precipitated in local areas of the glass. If the content is higher than 20wt%, it reverts to the defect range of traditional high boron core materials. During the high-temperature wire drawing and hot pressing stages, boron will continue to diffuse bidirectionally into the skin glass, destroying the dense silicon-oxygen network of the skin, causing Pb and Bi elements to accumulate on the surface of the skin, the GMCP single-channel resistance deviation to exceed 10%, the ion feedback noise to surge, and the weak common vertex electron tracks of the Migdall effect to be masked. This invention limits the low boron range to suppress the cross-interface migration of boron from the source of the formulation. Further preferred values are 12~18wt%.
[0033] Both La2O3 and Sm2O3 are lanthanide rare earth oxides. High field strength rare earth ions can stabilize the silicon-oxygen network structure and confine the high-temperature migration of boron and alkali metal ions. They can also synergistically regulate the glass softening temperature and the coefficient of thermal expansion in the 20-300℃ range, achieving matching with the thermal parameters of GMCP-specific skin glass. This enhances the resistance to crystallization and phase separation in the 600-900℃ range. If the total rare earth content is less than 20wt% and the Sm2O3 is less than 5wt%, the total rare earth content is insufficient, which cannot effectively confine the migration of ions within the network, and the diffusion of boron and rubidium / cesium ions across the interface is aggravated. At the same time, the coefficient of thermal expansion and softening temperature deviate from the matching window, resulting in inconsistent core-skin deformation during the drawing process, leading to delamination and hexagonal channel collapse. If the rare earth ions are more than 30wt% and the Sm2O3 is more than 10wt%, the high-temperature viscosity of the glass increases sharply, the difficulty of melting and clarifying increases significantly, rare earth silicate crystal phases are easily precipitated, crystal point defects are generated on the core surface, and mirror polishing cannot be achieved. At the same time, the glass acid dissolution rate is greatly reduced, and acid pickling and hole making residues are serious. The preferred concentrations of La2O3 are 22-28 wt%, and the preferred concentrations of Sm2O3 are 6-9 wt%.
[0034] BaO and SrO are alkaline earth metal oxides in the network structure, which can break a large number of Si-O-Si silicon-oxygen bonds to generate non-bridging oxygen, significantly improving the dissolution rate of dilute acid corrosion; they also work synergistically with rare earth oxides to fine-tune the coefficient of thermal expansion, balancing the high-temperature properties of the glass; and they help suppress high-temperature ion interface migration. If BaO is below 10wt% and SrO is below 5wt%, the number of non-bridging oxygens inside the glass is insufficient, the acid resistance stability cannot meet the Class 6 standard, the core material dissolves unevenly, and the local corrosion depth is insufficient; if BaO is above 20wt% and SrO is above 10wt%, the alkaline earth metal components are excessive, the silicon-oxygen network structure is loose, and surface salt precipitation and whitening are likely to occur when stored at room temperature; the high-temperature coefficient of thermal expansion exceeds the matching range, resulting in thermal mismatch with the outer glass, and the hot-pressed composite wire is prone to cracking and scrapping. BaO is further preferably 12~18wt%, and SrO is further preferably 6~9wt%.
[0035] In₂O₃ is the core rare-dispersed metal functional component for controllable acid etching in this invention. In a dilute acid environment, In… 3+ It can rapidly dissolve from the glass network, constructing interconnected nano-etching channels on the glass surface without forming a dense silica passivation film, achieving synchronous and uniform etching across the entire cross-section of the core material. If the content is below 2wt%, there are insufficient active sites for acid etching to create pores, resulting in sparse etching channels, significantly prolonged acid washing time, and incomplete removal of the core material. If the content is above 7wt%, the high In2O3 content easily precipitates metallic indium black spots under a weak reducing melting atmosphere, causing glass homogeneity defects and significantly increasing the raw material preparation cost. A further preferred content is 3~6wt%.
[0036] Rb₂O and Cs₂O are large-radius monovalent alkali metal oxides, completely replacing traditional small-radius alkali metals such as Na₂O and K₂O. Their large ionic radii weaken the chemical bond strength of the metal oxides (MO), leading to preferential hydrogen ion exchange during acid pickling and rapid formation of surface etching pores. The multi-element mixed alkali effect reduces the high-temperature viscosity of the glass and inhibits crystallization. Compared to Na₂O… + K + High-temperature interfacial diffusion capacity is significantly reduced. When the content of a single component is less than 5 wt%, the total alkali metal content of Rb₂O+Cs₂O is less than 10 wt%, resulting in a lack of ion exchange pore-forming sites, slow acid etching initiation speed, and poor corrosion uniformity. When the content of a single component is higher than 10 wt%, the total alkali metal content exceeds 18 wt%, and the gaps in the glass network are filled with a large amount of alkali metal, leading to poor weather resistance at room temperature and whitening of the surface due to the precipitation of rubidium and cesium salts after long-term storage. Excessive alkali metals will also exacerbate high-temperature interfacial diffusion and impair the helium permeation resistance and DME corrosion resistance of the glass coating. Rb₂O and Cs₂O are further optimized to 6~9 wt%.
[0037] To facilitate clarification during product preparation, Sb₂O₃ is added to the ingredients as a high-temperature melting clarifying agent. During the high-temperature stage, it decomposes and releases oxygen, eliminating micro-bubbles inside the glass and improving its homogeneity and light transmittance. Assuming the total amount of all raw materials mentioned above is 100%, its content accounts for 0.1~0.3% of the total raw materials. Below 0.1wt%, the clarification and defoaming effect is insufficient, resulting in numerous bubble defects inside the finished core rod. Above 0.3wt%, excess antimony oxide is easily reduced to precipitate elemental antimony, producing gray impurity particles that damage the mirror polishing effect of the core rod and reduce the adhesion of the subsequent Nb₂O₅ thin film to the substrate.
[0038] To balance the multiple properties of glass, including thermal matching, resistance to crystallization, controllable acid etching, and low ion diffusion, the mass fraction of the glass components in this core material preferably simultaneously satisfies one or more of the following ratios: The mass ratio of rare earth oxides to boron oxide is (La2O3+ Sm2O3) / B2O3=1.25~2.50, preferably 1.6~2.0. Rare earth oxides can suppress the high-temperature migration of boron. Within this range, the amount of boron diffusion at the core-skin interface can be significantly reduced, while avoiding excessive rare earths that cause glass refractory and crystallization.
[0039] The ratio of total alkaline earth metal oxides to total rare earth oxides is: (BaO + SrO) / (La2O3 + Sm2O3) = 0.69~1.2, preferably 0.8~1. Alkaline earth metals can generate a large amount of non-bridging oxygen, which can synergistically regulate the thermal expansion coefficient and softening temperature of glass with rare earths, achieve thermal matching with the glass body, and improve the overall acid dissolution rate.
[0040] The core glass of the gas microchannel plate described in this invention has the following performance indicators according to the following test methods: The softening temperature Tf of the core glass of this invention is ≥660℃, and the coefficient of thermal expansion at 20~300℃ is (82~87)×10⁻¹⁰, as tested according to GB / T7962.16-2010 Test Method for Colorless Optical Glass. -7 / ℃. After heat treatment in the temperature range of 600~900℃, the core glass samples were observed by XRD and SEM. No crystallization or phase separation was observed in the samples at 600~900℃, indicating good resistance to crystallization. Acid resistance stability was tested according to GB / T 7962.14-2010, and the acid dissolution rate was tested. The acid resistance stability was Class 6, indicating good acid solubility.
[0041] This invention also proposes a method for preparing a glass rod as the core material for a gas microchannel plate, comprising: First, the ingredients are mixed: Weigh out the raw materials, namely silicon dioxide, boron oxide, lanthanum oxide, barium oxide, strontium oxide, indium oxide, samarium oxide, rubidium carbonate, and cesium carbonate, according to the above weight percentages; add a clarifying agent, such as Sb2O3, at a weight of 0.1~0.3wt% of the above ingredients to remove bubble defects during the melting process; mix the above materials evenly.
[0042] Next is the preparation of pre-melted clinker: the above mixed batches are added into a quartz crucible in batches and held at 1200~1300℃ for the first melting to obtain a uniform pre-sintered clinker. This pre-sintering step can reduce the precipitation of bubbles in the subsequent high-temperature clarification stage.
[0043] The next step is high-temperature clarification melting: the above-mentioned calcined material is transferred into a high-purity platinum crucible with niobium dispersion, and the temperature is raised to 1450~1500℃ under the stirring condition of platinum-rhodium alloy stirring rod for the second melting. The stirring is continuous to ensure that the rare earth, alkali metal and alkaline earth components are uniformly dispersed and to avoid local component segregation, so as to obtain a homogenized glass melt.
[0044] Next is the extrusion molding of glass rods: the molten homogenized glass liquid is cooled to 1350~1400℃ and mechanically extruded to obtain a core glass blank rod with a preset outer diameter.
[0045] The next step is precision annealing: the glass rod is sent into an annealing furnace and heated to 500-580℃ at a rate of 1.5-3.0℃ / min, and held for 3-4 hours to eliminate internal thermal stress; then it is slowly cooled to room temperature at a rate of 0.5-1.5℃ / h to avoid cracking and edge chipping during subsequent processing, coating, and wire drawing.
[0046] Finally, precision shaping and polishing: the annealed glass blank rod is precision ground and mirror polished to obtain a finished core glass rod with uniform outer diameter, no scratches on the surface, and no free alkali precipitation, providing a qualified substrate for subsequent magnetron sputtering coating.
[0047] The present invention also proposes a glass rod for the core material of a gas microchannel plate, which is obtained by the above preparation method and can be used as an intermediate product.
[0048] To further suppress bidirectional interdiffusion of elements between the core glass and the skin glass during the bundle drawing and high-temperature hot pressing processes, and to ensure the uniformity of global resistance and long-term operational stability of the gas microchannel plate, this invention also provides a core glass rod for the gas microchannel plate. The surface of this core glass rod is coated with a Nb₂O₅ barrier film with a thickness of 50-200 nm. After the core glass rod coated with the Nb₂O₅ barrier film is combined with the skin glass, the interdiffusion width at the core-skin interface is ≤50 nm. The interdiffusion width is measured using aberration-corrected scanning transmission electron microscopy-high-angle annular dark-field imaging (STEM-HAADF) combined with electron energy loss spectroscopy (EELS) / energy dispersive spectroscopy (EDS) line scanning. Specifically, the process is as follows: A glass rod containing the core material is inserted into a lead-bismuth tubing and kept at 540℃ for 2 hours; a single core-skin composite wire is cut, and a TEM sample is prepared by ultrathin ion reduction perpendicular to the interface; three parallel wires at different positions are prepared as parallel samples; three complete and defect-free core-skin interfaces are selected from each sample for STEM-HAADF+EELS testing, with a nanowire scanning perpendicular to the interface and a step size of 3 nm; the concentration distribution curves of B, Pb, Bi, and La are recorded, and the maximum width of bidirectional interpenetration of elements is recorded in nm. In some specific tests of this invention, the composition of the lead-bismuth tubing, based on the mass percentage of oxides, includes: SiO2, 30~40wt%; Al2O3, 2~5wt%; PbO, 30~40wt%; Bi2O3, 12~18wt%; MgO, 1~5wt%; SrO, 1~4wt%; Cs2O and Rb2O combined, 2~4wt%; HfO2, 2~4wt%; Ta2O5, 3~5wt%.
[0049] This invention also proposes a coating method for a glass rod as the core material of a gas microchannel plate, comprising: First, the core glass rod substrate undergoes precision pretreatment: The polished core glass rod is ultrasonically cleaned sequentially with anhydrous ethanol and deionized water for 10–15 minutes each to remove oil, dust, and free alkali precipitates from the outer surface. After cleaning, it is dried in a vacuum oven at 80–100℃ for 30–40 minutes to completely remove surface-adsorbed moisture. Then, the core glass rod is clamped onto a rotating fixture within the magnetron sputtering chamber, and a two-stage pump system is used to evacuate the system to a base vacuum ≤5×10⁻⁶. -4 High-purity argon gas is introduced into the chamber, and an RF bias of 500±50V is applied to perform in-situ argon plasma ion etching to remove the nano-defect layer on the glass surface, thereby improving the adhesion between the Nb2O5 film and the glass substrate interface. The preferred plasma etching process is argon plasma etching at an RF bias of 500V for 4–6 minutes.
[0050] Next is the pre-conditioning of the chamber atmosphere and target alignment: keep the chamber sealed, continuously pump vacuum, and stabilize the background vacuum to ≤5×10⁻⁶. -4Pa; High-purity argon gas is introduced into the chamber as the sputtering carrier gas, with a preferred flow rate of 30-60 sccm and a stable working pressure of 0.3-0.8 Pa. Pre-gas is introduced, such as for 10 minutes, to remove water vapor and impurities from the chamber; 99.99% pure niobium metal is selected as the target material, and the target-substrate distance between the target material and the outer surface of the core glass rod is adjusted to 60-100 mm; The core glass rod is controlled to rotate uniformly along the axial direction at a speed of 5-10 r / min to ensure uniform 360° circumferential film thickness without local thin areas or incomplete deposition defects.
[0051] Next, reactive magnetron sputtering is used to deposit a dense Nb2O5 barrier film with a thickness of 50~200nm on the surface of the core glass rod: high-purity argon gas is introduced into the chamber simultaneously with high-purity oxygen gas as the reactive oxidizing gas, and the oxygen-argon volume flow rate ratio is controlled at 1:8 to 1:5; the RF sputtering power is turned on, and the sputtering power is 120~200W; the film thickness is precisely controlled by the deposition time; specifically, the sputtering time for a 50nm Nb2O5 film is 15~25min, and the sputtering time for a 200nm Nb2O5 film is 60~90min; this step can coat the outer periphery of the core glass rod with a continuous, pinhole-free, high-density Nb2O5 high-temperature ion diffusion barrier film.
[0052] The next step is low-temperature stress annealing: After sputtering, the sputtering power supply is turned off, and the argon and oxygen supply is cut off, allowing the chamber to cool naturally to below 120°C; high-purity nitrogen is introduced into the chamber to break the vacuum, and the coated core glass rod is removed; it is then placed in a temperature-controlled muffle furnace and heated to 400-450°C at a rate of 0.5-5°C / min, preferably 1.5°C / min, and held at this temperature for 1-3 hours for low-temperature annealing, preferably 2 hours, to release the residual compressive stress inside the film and prevent the film from cracking, warping, or peeling during subsequent high-temperature drawing and hot pressing processes at 1350-1500°C.
[0053] Finally, the film thickness was tested and determined: the film thickness was measured at multiple points along the circumference of the glass rod using a profilometer to confirm that its overall thickness was stable in the range of 50-200 nm; the film was observed to be free of pinholes, cracks, and peeling by scanning electron microscopy; it was then combined with the skin material, and verified by spherical aberration-corrected STEM-HAADF combined with EDS line scanning. The interdiffusion width at the composite core-skin interface was ≤50 nm, thus completing the preparation of the coated core material glass rod.
[0054] The present invention also proposes a gas microchannel plate, which is prepared by combining a sheath glass tube and a core glass rod with a surface coated with a dense Nb2O5 barrier film, and then by a process of bundling, drawing, hot pressing and acid etching.
[0055] The present invention also proposes the application of the aforementioned gas microchannel plate core material glass in the preparation of gas microchannel plates, Migdall effect detection devices, or light dark matter detection devices.
[0056] The present invention will be further described below with reference to specific embodiments, but this should not be construed as a limitation on the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention still fall within the scope of protection of the present invention.
[0057] Unless otherwise specified, all materials and reagents mentioned below are commercially available products well known to those skilled in the art; unless otherwise specified, all methods described are methods known in the art. Unless otherwise defined, the technical or scientific terms used should have the ordinary meaning understood by those skilled in the art to which this invention pertains.
[0058] Examples 1-6 This embodiment provides a core glass rod for a gas microchannel plate, and its preparation steps are as follows: 1) Raw material batching and mixing: Silicon dioxide, boron oxide, lanthanum oxide, barium oxide, strontium oxide, indium oxide, samarium oxide, rubidium carbonate, and cesium carbonate are used as basic raw materials and weighed according to the mass percentages shown in Table 1. Rubidium carbonate and cesium carbonate are pre-dried at 120℃ for 2 hours to remove water of crystallization. After the raw materials are weighed, 0.2wt% of Sb2O3 of the total amount of the aforementioned raw materials is added as a clarifying agent. All powders are put into a mixer and thoroughly dry-mixed for 30 minutes to obtain a uniform batch.
[0059] 2) Preparation of pre-melted clinker: The batch material is added to the quartz crucible in three batches, heated to 1250℃ and held for 2 hours for pre-melting to obtain uniform clinker glass without large lumps.
[0060] 3) High-temperature melting and clarification: The above-mentioned clinker is transferred into a niobium-dispersed high-purity platinum crucible and heated to 1480℃ and kept at a constant temperature for 4 hours; during which, a platinum-rhodium alloy stirring rod is used to continuously stir at a uniform speed for 2 hours.
[0061] 4) Extrusion molding of glass rods: After melting, the temperature is reduced to 1380℃, and the glass blank rods with uniform outer diameter are obtained by uniform extrusion using a vertical extrusion device.
[0062] 5) Annealing to relieve internal stress: Adjust the heating rate of the annealing furnace to 2℃ / min, heat to 550℃ and hold for 3.5h; then slowly and uniformly cool down to room temperature at 1℃ / h.
[0063] 6) Precision shaping and polishing: After annealing, the outer diameter of the glass blank rod is precision ground and mirror polished to remove surface irregularities and free alkali precipitation layer, resulting in a finished core glass rod with a smooth surface and an outer diameter tolerance of ≤1μm, which is used as a magnetron sputtering substrate.
[0064] 7) Substrate pretreatment: The polished mandrel was ultrasonically cleaned with anhydrous ethanol for 12 min and then ultrasonically cleaned with deionized water for 12 min; dried in a vacuum oven at 90℃ for 35 min; then placed into the sputtering chamber rotating fixture, and the base vacuum was evacuated to 4×10⁻⁶. - 4 Pa, 500V argon plasma in-situ etching for 5 min.
[0065] 8) Chamber atmosphere and tooling adjustment: Ar flow rate of 40 sccm, stabilize chamber pressure of 0.5 Pa, pre-ventilate for 10 min; select 99.99% high purity niobium metal target, target-substrate distance of 80 mm; mandrel axial uniform rotation of 8 r / min to ensure uniform 360° circumferential coating.
[0066] 9) Reactive sputtering deposition of Nb2O5 film: oxygen to argon flow rate ratio 1:7, RF sputtering power 160W; continuous deposition for 50min; forming a continuous and dense Nb2O5 barrier layer on the outer periphery of the mandrel.
[0067] 10) Low-temperature stress annealing: After coating, the chamber is cooled to below 120°C, nitrogen is used to break the vacuum, and the mandrel is removed; it is then placed in a muffle furnace with programmed temperature control, and the temperature is increased to 450°C at 1.5°C / min and held for 2 hours.
[0068] 11) Inspection and judgment: a. Use a step meter to perform multi-point inspection. If the film thickness is between 50 and 200 nm, it is considered qualified; b. SEM observation shows no pinholes or cracks; c. Bundle the coated core rod and the skin glass tube together, draw and hot press them into composite wires, and use spherical aberration corrected STEM-HAADF+EDS line scan to test the interdiffusion width of the core-skin interface.
[0069] The formulations of the core glass and the physicochemical properties of the core glass rods in each embodiment are detailed in Table 1.
[0070] Comparative Examples 1-5 The difference between Comparative Examples 1-5 and Example 1 lies in the glass formulation; the other preparation processes are the same as in Example 1. The formulations and physicochemical properties of the glasses in Comparative Examples 1-5 are shown in Table 2.
[0071] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the annealing temperature of Comparative Example 6 is 280°C, while the other preparation processes and glass formulations are the same as those of Example 1.
[0072] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that Comparative Example 7 did not use magnetron sputtering to deposit the barrier film, while the other preparation processes and glass formulations were the same as in Example 1.
[0073] Table 1
[0074] Table 2
[0075] Note: In Tables 1 and 2 above, the letters A through E representing performance have the following meanings: A represents the coefficient of thermal expansion of the core glass at 300℃, in units of ×10⁻¹⁰. -7 / ℃; B represents the softening temperature T of the core glass. f The unit is ℃; C represents the acid resistance stability of the core glass; D represents the anti-crystallization performance; E represents the interdiffusion width at the core-skin interface, in nm; F represents the film thickness, in mm.
[0076] As can be seen from the test data of the examples in Table 1, the gas microchannel plate core glass prepared by the present invention has excellent performance, with high acid etching rate, good anti-crystallization performance, and softening temperature and linear expansion coefficient as shown in Examples 1 to 6.
[0077] In Comparative Example 1, the excessive doping of cesium and rubidium elements in the system significantly reduced the softening temperature of the glass system, resulting in a mismatch between the softening temperature of this glass and that of the sheet glass, leading to extremely poor compatibility. During the wire drawing process, this temperature mismatch defect directly caused a significant deterioration in the roundness of the gas microchannel plate (MCP) channels, resulting in substandard channel forming accuracy. Ultimately, this severely affected the working gain performance of the gas microchannel plate, making it unable to meet product usage requirements.
[0078] Comparative Example 2, by reducing the doping content of barium oxide (BaO) and indium oxide (In2O3), directly led to a significant decrease in the acid etching rate of the glass substrate. This reduced etching rate significantly increased the difficulty of the MCP etching process, requiring a longer etching time to achieve the standard etching effect. This unconventional process adjustment not only reduced overall production efficiency but also caused deterioration in the overall structural stability of the sheet material, leading to deformation, performance fluctuations, and other adverse problems, which are detrimental to stable mass production and use.
[0079] In Comparative Example 3, the excessive addition of lanthanum oxide (La₂O₃) and samarium oxide (Sm₂O₃) disrupted the compositional balance of the glass system, significantly weakening its resistance to crystallization and making it highly susceptible to crystallization defects during the forming process. Crystallization leads to poor uniformity of the glass material, deterioration of its mechanical and forming properties, and significantly increases the difficulty of the wire drawing process, making it difficult to form MCP preforms with complete structure and uniform properties.
[0080] In Comparative Example 4, the boron (B) content was too high. In Comparative Example 5, potassium and sodium were used to replace the original cesium and rubidium elements. Both composition schemes resulted in excessively rapid element diffusion rates between the core and skin glass during the wire drawing process, leading to severe interpenetration at the core-skin interface. This defect significantly reduces the corrosion resistance of the microchannel inner wall of the finished gas microchannel plate. In actual use, the inner wall of the channel is easily corroded and worn, directly shortening the overall service life of the gas microchannel plate and reducing product reliability and service life.
[0081] The glass composition of Comparative Example 6 was exactly the same as that of Example 1, but its annealing temperature was set to 280°C, deviating from the optimal annealing process parameters. This low-temperature annealing process could not effectively eliminate the internal stress generated during glass forming. After annealing, the samples frequently suffered structural damage such as cracking, edge chipping, and breakage during subsequent processing steps such as cutting, grinding, and finishing, making it impossible to obtain structurally intact and valid samples that met the testing standards. Furthermore, the finished samples that had not undergone mechanical processing also exhibited spontaneous cracking, resulting in extremely poor structural stability and making it impossible to conduct subsequent performance tests.
[0082] Comparative Example 7 did not employ magnetron sputtering to prepare an Nb₂O₅ coating on the glass rod substrate surface. The lack of a protective coating resulted in a significantly increased thickness of the interdiffusion layer between the core and skin glass layers, leading to uncontrolled element diffusion. STEM-HAADF+EELS testing showed that the maximum width of bidirectional interdiffusion reached 712 nm. This structural defect resulted in insufficient protection of the microchannel inner wall of the formed gas microchannel plate, failing to meet the core requirements of corrosion resistance and erosion resistance for microchannel inner walls in practical applications, thus rendering the product's performance substandard.
[0083] The technical features in the claims and / or specification of this invention can be combined, and the combination is not limited to the combinations obtained through reference in the claims. Technical solutions obtained by combining the technical features in the claims and / or specification are also within the scope of protection of this invention.
[0084] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A glass core material for a gas microchannel plate, characterized in that, Based on the mass percentage of oxides, it is composed of the following components: SiO2, 5~15wt%; B2O3, 10~20wt%; La2O3, 20~30wt%; BaO, 10~20wt%; SrO, 5~10wt%; In2O3, 2~7wt%; Sm2O3, 5~10wt%; Rb2O, 5~10wt%; Cs2O, 5~10wt%.
2. The gas microchannel plate core glass according to claim 1, characterized in that, Based on the mass percentage of oxides, it is composed of the following components: SiO2, 8~12wt%; B2O3, 12~18wt%; La2O3, 22~28wt%; BaO, 12~18wt%; SrO, 6~9wt%; In2O3, 3~6wt%; Sm2O3, 6~9wt%; Rb2O, 6~9wt%; Cs2O, 6~9wt%.
3. The gas microchannel plate core glass according to claim 1, characterized in that, In the core glass, the mass ratio of the sum of La2O3 and Sm2O3 to B2O3 is 1.25~2.50; the ratio of the sum of the mass of BaO and SrO to the sum of the mass of La2O3 and Sm2O3 is 0.69~1.
20.
4. The gas microchannel plate core glass according to claim 3, characterized in that, In the core glass, the mass ratio of the sum of La2O3 and Sm2O3 to B2O3 is 1.6~2.0; the ratio of the sum of the mass of BaO and SrO to the sum of the mass of La2O3 and Sm2O3 is 0.8~1.
0.
5. The gas microchannel plate core glass according to any one of claims 1 to 4, characterized in that, Its softening temperature T f The coefficient of thermal expansion is 82×10⁻⁶ at temperatures ≥660℃ and between 20 and 300℃. -7 / ℃ ~87×10 -7 / ℃, no crystallization or phase separation at 600~900℃; the acid resistance stability of the core glass tested according to GB / T 7962.14-2010 is Class 6.
6. A method for preparing a glass rod as the core material for a gas microchannel plate, characterized in that, It includes the following steps: S1. The glass formulation for the gas microchannel plate core material according to any one of claims 1 to 5 is prepared by adding a clarifying agent of 0.1 to 0.3 wt% of the total mass of the formulation to the formulation and mixing it evenly. S2 The mixture is placed in a quartz crucible and first melted at 1200~1300℃ to obtain pre-sintered clinker; S3 places the calcined material in a high-purity platinum crucible with niobium dispersion, and heats it to 1450~1500℃ for a second melting under the stirring condition of a platinum-rhodium alloy stirring rod. After clarification, a homogenized glass melt is obtained. S4 cools the homogenized glass melt to 1350~1400℃ and then mechanically extrudes it to obtain a core glass blank rod. S5 heats the core glass blank rod to 500-580℃ at a rate of 1.5-3.0℃ / min, holds it at that temperature for 3-4 hours for annealing, and then cools it to room temperature at a rate of 0.5-1.5℃ / h. The S6 precision shaping and mirror polishing process yields the core glass rod.
7. A method for coating a glass rod as the core material of a gas microchannel plate, characterized in that, It includes the following steps: S1 Surface treatment: The core glass rod prepared by the preparation method described in claim 6 is cleaned, dried and subjected to plasma etching pretreatment; S2 uses niobium as the target material and a reactive magnetron sputtering process to deposit a Nb2O5 barrier film on the surface of the core glass rod in an atmosphere of mixed argon and oxygen. The thickness of the barrier film is 50~200nm. S3 performs low-temperature stress annealing on the coated core glass rod by holding it at 400~450℃ for 1~3 hours.
8. The coating method according to claim 7, characterized in that, In the reactive magnetron sputtering process, the argon flow rate is 30~60 sccm, the working pressure is 0.3~0.8 Pa, the oxygen-argon volume flow rate ratio is 1:8~1:5, the RF sputtering power is 120~200 W, the target-substrate distance is 60~100 mm, and the axial rotation speed of the core glass rod is 5~10 r / min.
9. The coating method according to claim 7, characterized in that, The pretreatment includes: ultrasonic cleaning with anhydrous ethanol and deionized water for 10-15 min respectively, followed by vacuum drying at 80-100℃ for 30-40 min; the plasma etching is performed with argon plasma etching at 500V RF bias for 4-6 min.
10. A glass rod as the core material for a gas microchannel plate, characterized in that, It is obtained by the preparation method described in claim 6.
11. The glass rod for the core material of the gas microchannel plate according to claim 10, characterized in that, Its surface is coated with an Nb2O5 barrier film with a thickness of 50~200nm; after the core glass rod coated with the Nb2O5 barrier film is combined with the skin material, the interdiffusion width at the core-skin interface is ≤50nm.
12. A gas microchannel plate, characterized in that, The gas microchannel plate is prepared by combining a sheath glass tube and a core glass rod as described in claim 11, followed by a bundling, drawing, hot pressing, and acid etching process.
13. The application of a gas microchannel plate core material glass according to any one of claims 1 to 5 in the preparation of gas microchannel plates, Migdall effect detection devices or light dark matter detection devices.